1999
DOI: 10.1128/aem.65.12.5541-5545.1999
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Methanogen Biomass by Quantitation of Coenzyme M

Abstract: Determination of the role of methanogenic bacteria in an anaerobic ecosystem often requires quantitation of the organisms. Because of the extreme oxygen sensitivity of these organisms and the inherent limitations of cultural techniques, an accurate biomass value is very difficult to obtain. We standardized a simple method for estimating methanogen biomass in a variety of environmental matrices. In this procedure we used the thiol biomarker coenzyme M (CoM) (2-mercaptoethanesulfonic acid), which is known to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The quantity of CoM determined in RG east sediments corresponds to~3 ¥ 10 3 methanogen cells g -1 dry weight sediment, when converted using the CoM cell -1 values previously determined for Methanosarcina barkeri str. Fusaro when grown on acetate (Elias et al, 1999). It is important to note that it has been suggested that CoM may be involved in the AOM (Hallam et al, 2004); however, this hypothesis remains untested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantity of CoM determined in RG east sediments corresponds to~3 ¥ 10 3 methanogen cells g -1 dry weight sediment, when converted using the CoM cell -1 values previously determined for Methanosarcina barkeri str. Fusaro when grown on acetate (Elias et al, 1999). It is important to note that it has been suggested that CoM may be involved in the AOM (Hallam et al, 2004); however, this hypothesis remains untested.…”
Section: Resultsmentioning
confidence: 99%
“…Coenzyme M is present in all methanogens and is involved in the final steps of methane formation, accepting methyl groups from methylcobalamin to form methylcoenzyme M, which is subsequently reductively demethylated, yielding methane (Taylor and Wolfe, 1974). The concentration of CoM in pure cultures of taxonomically and metabolically diverse methanogens is proportional to the growth status of the cells, the concentration of viable cells, and to cellular protein (Elias et al ., 1999). Coenzyme M is labile and not likely to be preserved in environmental samples, as indicated by an approximate 46–83% decrease in detectable CoM in a variety of environmental samples following a single freeze‐thaw cycle when compared with unfrozen samples (Elias et al ., 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coenzyme M and mcrA gene copy numbers are the biomarkers of methaogens [ 23 ] and Co-M only found in methanogens. BES is a structural analogue of Co-M and application of it makes competitive inhibition for methyl group during methanogenesis and thereby inhibits methanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the content of CoM varies with the growth phase of methanogens and it is not accurate in samples after freezing (Elias et al 1999).…”
Section: Research and Development Of The Hasl Systemmentioning
confidence: 99%